Antileishmanial Activity of Natural Diterpenoids: A Comprehensive Review - Mirzania, Foroogh; Ghasemian Yadegari, Javad; Salimikia, Iraj (Current Organic Chemistry, 2023)
Infections that occur by protozoa are a chief universal issue for health, with wide endemicity in the involved areas. In the absence of a vaccine, there is an immediate requirement for efficient medications to replace those in common applications. However, their low effectiveness, lengthy treatment regimen, high poisoning, detrimental side effects of drugs and expensive prices require the need for superior medicine; these are all the factors that make leishmaniasis vaccines unavailable in the near future. Therefore, there is an immediate requirement to discover unique antileishmanial drugs with fine power and preferable remedial profile. Even though most of the medications are still derived from medicinal plant origins, the concern in higher plants as the origin of new bioactive natural compounds has been enhanced in recent years. The present study is a review of reports of naturally occurring diterpenoids extracted from plants and exhibiting anti-leishmaniasis activity. This review article refers to 25 plant species, their families, the portion used and the type of extract investigated. It also includes 88 diterpenoids extracted and identified from higher plant species, which are classified into chemically and structurally suitable groups. A number of recent reports and anti-leishmaniasis activities on natural compounds are discussed. This article provides a good overview of the future of leishmaniasis drug discovery.
Keywords: terpene